KAJIAN FAKTOR-FAKTOR YANG MEMPENGARUHI PENYALURAN KREDIT PERBANKAN: STUDI KASUS PADA PD. BPR DI JAWA TENGAH PERIODE 2011-2012 - Umirotul Fauziah, 10.05.52.0127; Masdjojo, Gregorius N. (Students Journal of Accounting and Banking, 2014)
This research aims to analyze factors which affect the Credit that granted by bank, especially in Regional Rural Banks Company, Central Java. These factors include the Customer Saving, Capital Adequacy Ratio, Non Performing Loan and the Inter-bank Liabilities. In this study, researchers used purposive sampling and obtain samples of 24 banks. The data used in the form of quarterly financial statements. The method used in the estimation is panel data regression analysis. software used in the data processing is Eviews 7.0. The results of the panel data estimation using Fixed Effect method (FEM) indicates that the customer saving positive and significant effect on the Credit, Capital Adequacy RatioÂ has significant negative effect on Credit, while the Non Performing Loan and Inter-bank liabilities Loans has not significant effect on the PD BPR in Central Java, 2011-2012. Keywords: Customer Saving, Capital Adequacy Ratio, Non-Performing Loans, Inter-Bank Liabilities and Credit